THE EFFORTS OF KING ABDULLAH II BIN AL HUSSEIN TO PROTECT ISLAMIC SANCTITIES (World Science, 2019)
The purpose of this study was to present the efforts of King Abdullah II to protect the Islamic shrines, and this was done using a historical approach and a descriptive analytical approach that identifies the origins of the Hashemites and their ongoing efforts to restore the Islamic shrines, then it was first identified and the second reconstruction of the Hashemites. Finally, third, King Abdullah II's efforts were made to monitor the Hashemite ancestors in restoring and protecting Islamic and Christian holy sites, and at the end of the study, potential outcomes of King Abdullah II's efforts to restore and protect Islamic holy sites were identified. He called for a series of results, the most important of which is that King Abdullah II reiterated his real and practical interest in restoring and protecting Islamic holy places after the campaign of his Hashemite ancestors.